Potential Radiation Impact of the Burial of the “Klivazh” Facility on the Yunkom Mine - Yakovliev, Yevhenii; Chumachenko, Sergii; Morsch, Yevhenii; Romanyuk, Valentin; Nikitin, Anatolii (My University, 2020)
Today, the issues of assessing natural and man-made risks in the area of the Joint Forces operation related to the flooding of the mine by Yunk are relevant. The risks of groundwater contamination and groundwater with radionuclides from the “Klivazh”facility, which was formed as a result of an underground nuclear explosion, increase in the absence of the pumping possibility of mine water from this mine. Radiation threats caused by the passive flooding of this facility create a number of negative consequences for the territories controlled by Ukraine. Therefore, there is an urgent need to assess the risk of contamination of the surrounding areas with radionuclides cesium-137, strontium-90 from the “Klivazh”facility. Given the existing hybrid war in eastern Ukraine, the solution to this problem can be considered as an element of analytical assessment of the predicted consequences of the “environmental war” against Ukraine.
Keywords: the ecological and geological environment; nuclear explosion; groundwate; contamination; the geological conditions; migration of radionuclides; еколого-геологічне середовище; підземні води; геологічні умови; ядерний вибух; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки